2021
DOI: 10.3389/fneur.2021.678245
|View full text |Cite
|
Sign up to set email alerts
|

Widespread Disruptions of White Matter in Familial Multiple Sclerosis: DTI and NODDI Study

Abstract: Diffusion tensor imaging (DTI) is a noninvasive, quantitative MRI technique that measures white matter (WM) integrity. Many brain dimensions are heritable, including white matter integrity measured with DTI. Family studies are valuable to provide insights into the interactive effects of non-environmental factors on multiple sclerosis (MS). To examine the contribution of familial factors to the diffusion signals across WM microstructure, we performed DTI and calculated neurite orientation dispersion plus densit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 70 publications
0
16
0
1
Order By: Relevance
“…Thalamic radiation changes were also observed, as NDI of left anterior and posterior thalamic radiation was reduced 29,34 . Two of these studies also reported specific pathways, including the corpus callosum, with increased ODI 27,29 . Hagiwara et al and Kato et al focused on the ISOVF of several NAWM tracts 31,33 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thalamic radiation changes were also observed, as NDI of left anterior and posterior thalamic radiation was reduced 29,34 . Two of these studies also reported specific pathways, including the corpus callosum, with increased ODI 27,29 . Hagiwara et al and Kato et al focused on the ISOVF of several NAWM tracts 31,33 .…”
Section: Resultsmentioning
confidence: 99%
“…Participants were age‐matched in four studies, 24,28,37,39 sex‐matched in one study 36 . Meanwhile, 15 studies controlled for both age and gender 16,18,23,26,27,29–31,33–35,40–43 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…DTI can analyze the dispersion movement of water molecules in tissues in three-dimensional space and non-invasively observe the changes in WM structure and fiber bundles in the brain ( 15 ), which is used to study the pathophysiological changes in the early brain ( 16 ). Based on the advantages of voxel and trajectory analysis, tract-based spatial statistics (TBSS) has been widely applied in studies of various neurological diseases, such as Parkinson's disease ( 17 ), chronic spinal cord injury in children ( 18 ), multiple sclerosis ( 19 ), schizophrenia ( 20 ), and preoperative evaluation of tumor ( 21 ). Macey et al ( 22 ) showed that OSA is more likely to damage WM fibers (bilateral cingulate, right terminal striatum) in women, and this differential damage helps explain the sex differences in symptoms, particularly anxiety and depression.…”
Section: Introductionmentioning
confidence: 99%
“…Diffusion imaging technology (DTI) can noninvasively display brain network connectivity and functional status without exogenous stimulation or tasks. It has been widely used in the study of neuropsychiatric diseases, such as Alzheimer's disease, multiple sclerosis, and schizophrenia ( 6 8 ). As mentioned earlier, the cerebellum may be involved in the coordination of cognitive functions through cerebellar fiber circuits.…”
Section: Introductionmentioning
confidence: 99%